Effect of framework soldering on the deformation of implant abutments after framework seating - Mendes, Stella de N. C.; Edwards Rezende, Carlos E.; Moretti Neto, Rafael T.; Sousa, Edson Antonio Capello [UNESP]; Henrique Rubo, José (Wolters Kluwer, 2013)
Introduction: Passive fit has been considered an important requirement for the longevity of implant-supported prostheses. Among the different steps of prostheses construction, casting is a feature that can influence the precision of fit and consequently the uniformity of possible deformation among abutments upon the framework connection. Purpose: This study aimed at evaluating the deformation of abutments after the connection of frameworks either cast in one piece or after soldering. Materials and Methods: A master model was used to simulate a human mandible with 5 implants. Ten frameworks were fabricated on cast models and divided into 2 groups. Strain gauges were attached to the mesial and distal sides of the abutments to capture their deformation after the framework’s screw retentions were tightened to the abutments. Results: The mean values of deformation were submitted to a 3-way analysis of variance that revealed significant differences between procedures and the abutment side. The results showed that none of the frameworks presented a complete passive fit. Conclusion: The soldering procedure led to a better although uneven distribution of compression strains on the abutments.